Generalized Derivations Acting as Homomorphisms and Anti-Homomorphisms on Lie Ideals of Prime Rings - Paul, Akhil Chandra; Chakraborty, Sujoy (GANIT: Journal of Bangladesh Mathematical Society, 2016)
Let U be a non-zero square closed Lie ideal of a 2-torsion free prime ring R and f a generalized derivation of R with the associated derivation d of R. If f acts as a homomorphism and as an anti-homomorphism on U, then we prove that d = 0 or U Z(R), the centre of R. GANIT J. Bangladesh Math. Soc.Vol. 35 (2015) 73-77